Concentration of Patents from Government Financed Research in Industry - Watson, Donald Stevenson; Holman, Mary A. (The Review of Economics and Statistics, 1967)
HE ownership of resulting from T government financed research and development constitutes a very controversial problem. The federal government mainly the Department of Defense (DOD) has permitted industrial firms to obtain the patent rights to most of the inventions emerging from its contract research, under the so-called with the government acquiring royaltyfree licenses on the inventions. Our task here is an empirical investigation of one of the issues in the controversy over federal patent policy, namely, the concentration of resulting from the operation of the license policy. One of the strongest objections to the license policy rests on the belief that it causes undue concentration of economic power. The objection has been raised repeatedly by attorneys general, by legislators, and by economists who favor the so-called ' under which the government retains ownership of resulting from its contract research. From records of the United States Patent Office, we have compiled data for the period 1946 to 1962 on the numbers of assigned to business firms that have been the research and development (R and D) for the Atomic Energy Commission (AEC), the Department of Defense, and the National Aeronautics and Space Administration (NASA). The data are neither estimates nor samples; they are complete counts. The three agencies account for nearly all of the issued under the license policy to contractors. Henceforth, we shall refer to these as license-policy patents. We also have data on the private patents resulting from the company financed R and D of the same contractors. The major R and D contractors are 177 business firms that were among the first 100 of DOD in any fiscal year from 1955 to 1962, or who had contract awards of $2 million or more from the AEC or from NASA.2 Of these 177 firms, 40 are among the first 100 in Fortune's list for 1962. Another 49 are among Fortune's 500 companies. A further 36 have been officially stamped as small businesses. With the exception of a few of the bigger chemical and oil companies that have done little or no research for the federal government, the names of nearly all the Schumpeterian giants of American industry are on our list. By treating each firm and its subsidiaries as a unit, we overstate patent concen* The research underlying this article was supported by a grant (NsG 425) from the National Aeronautics and Space Administration to The George Washington University. 1 Department of Justice, Investigations of Government Patent Practices and Policies: Report and Recommendations of the Attorney General to the President 1 (Washington, D.C.: U.S. Government Printing Office, 1947), 37; Report of the Attorney General Pursuant to Section 708 (e) of the Defense Production Act of 1950, as Amended (Nov. 9, 1956, mimeo.); Clair Wilcox, Public Policies Toward Business (Homewood, Ill.: Richard D. Irwin, 1960), 191; Walter Adams and Horace M. Gray, Monopoly in America: The Government as Promotor (New York: Macmillan, 1955), 47, 94, and 148-152. Testimony against the license policy and in favor of the title policy was given to a Senate subcommittee in 1963 by Horace M. Gray, Robert F. Lanzillotti, Wassily W. Leontief, Richard R. Nelson, and Lee E. Preston. See Aspects of Government Patent Policies, Hearings before a Subcommittee of the Select Committee on Small Business, United States Senate, 88th Congress, First Session, Impact of Government Patent Policies on Economic Growth, Scientific and Technological Progress, Competition, and Opportunities for Small Business, March 7, 8, 13, and 14, 1963 (Washington, D.C.: U.S. Government Printing Office, 1963). Only Leontief (p. 236), however, addressed himself specifically to the question of concentration. 2 Department of Defense, 500 Contractors Listed According to Net Value of Military Prime Contract Awards for Experimental, Development Test and Research Work (Fiscal years 1955 through 1962, mimeo.); and Files of the Atomic Energy Commission and published reports of the National Aeronautics and Space Administration. 'Usually, government employees are required to assign title to the government. However, if a government employee, with his own resources, produces an invention that his agency wants, the government frequently files the patent application in exchange for a royalty-free license. Also, if an agency does not want a government financed invention made by an employee, the employee often is permitted to acquire title. Regulations governing employees were tightened in 1950. This fact and the relative growth of contract research are the causes of the decline in the number of licenses from employees after 1950.